Semiquantitative acid–base analysis in hypokalemic dogs with immune-mediated hemolytic anemia - Philp, Helen S.; Epstein, Steven E.; Hopper, Kate (Frontiers in Veterinary Science, 2025)
ObjectiveTo describe and compare the traditional and semiquantitative acid–base status of dogs with immune-mediated hemolytic anemia (IMHA) and hypokalemia to those with normokalemia.MethodsMedical records of dogs with IMHA from a single institution over a 10-year period from January 1st, 2012 to December 31st, 2021 were retrospectively reviewed. Dogs were included if they met diagnostic criteria for IMHA based on the 2019 ACVIM consensus guidelines and had at least 1 blood potassium concentration measurement performed within 24 h of initial presentation. The dogs were divided into normokalemic and hypokalemic groups. Hypokalemia was categorized as mild (3–3.5 mEq/L [3–3.5 mmmol/L]), moderate (2–2.9 mEq/L [2–2.9 mmol/L]), or severe (<2 mEq/L [<2 mmol/L]). Population data, clinicopathologic data, and outcome were collected and recorded. Traditional and semiquantitative acid–base diagnoses were attributed to patients with sufficient data.Results305 client-owned dogs with IMHA met the inclusion criteria. 186 dogs (61.0%) were normokalemic and 119 (39.0%) were hypokalemic (blood potassium concentration ≤ 3.5 mEq/L [≤ 3.5 mmol/L]) on presentation. The median blood potassium concentration in the hypokalemic group was 3.2 mEq/L (3.2 mmol/L) (interquartile range: 2.8–3.4 mEq/L [2.8–3.4 mmol/L]). Hypokalemia was mild in 78/119 (65.5%) dogs, moderate in 40/119 (33.6%) and severe in 1/119 (0.84%) cases. Metabolic acidosis was the most common traditional acid–base disorder identified in both normokalemic (26/82, 31.7%) and hypokalemic (44/92, 47.8%) dogs but the proportion was significantly higher in the hypokalemic group (p = 0.03). The semiquantitative approach identified acid–base abnormalities in 82/83 (98.8%) hypokalemic dogs. The most common abnormalities among the hypokalemic group were an unmeasured ion effect (74/83, 89.2%) and an alkalotic albumin effect (69/83, 83.1%). In the normokalemic group, the semiquantitative approach identified acid–base abnormalities in 62/63 (98.4%) dogs with unmeasured ions (55/63, 87.3%) and an alkalotic albumin effect (42/63, 66.7%) being the most common. Survival to discharge was significantly lower in the hypokalemic dogs (85/119, 71.4%) compared to the normokalemic population (163/186, 87.6%) (p = 0.02).ConclusionHypokalemia is common in dogs with IMHA within the first 24 h of presentation and is associated with a variety of acid–base abnormalities. Hypokalemic dogs with IMHA appear more likely to develop metabolic acidosis and less likely to survive to hospital discharge.